2020
DOI: 10.3390/ani10010174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Hatchery Byproduct Mixture on Growth Performance and Digestible Energy of Various Hatchery Byproduct Mixtures in Nursery Pigs

Abstract: The objectives were to determine effects of a hatchery byproduct mixture (HBM) on growth performance and to measure digestible energy concentrations in various HBM. In the growth performance experiment, 96 pigs (initial body weight = 9.6 ± 0.8 kg) were assigned to 4 dietary treatments in a randomized complete block design with 6 blocks. Each treatment consisted of 6 replicate pens with 4 pigs comprising 2 barrows and 2 gilts. Pigs were fed graded concentrations of HBM at 0%, 3.33%, 6.67%, and 10.00% for 14 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In the current experiment, the CP concentrations in 4 HBPs ranged from 31.2 to 60.0%, which were closed to the values (32.2–66.3%) reported in previous experiments ( Sung et al, 2019 ; Sung et al, 2020 ; Sung and Kim, 2020 ). These results indicate that HBPs used in the current experiment are similar to those used in previous experiments.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the current experiment, the CP concentrations in 4 HBPs ranged from 31.2 to 60.0%, which were closed to the values (32.2–66.3%) reported in previous experiments ( Sung et al, 2019 ; Sung et al, 2020 ; Sung and Kim, 2020 ). These results indicate that HBPs used in the current experiment are similar to those used in previous experiments.…”
Section: Discussionsupporting
confidence: 79%
“…The GE concentrations of MIX used in the current experiment were similar or lower than those reported in previous studies ( Rasool et al, 1999 ; Mehdipour et al, 2009 ; Sung et al, 2019 ). The variable GE concentrations in MIX result from different sources and inclusion amounts of individual HBPs, which are largely dependent of the hatchability in the commercial hatchery ( Rasool et al, 1999 ; Thaler and Holden, 2010 ; Sung and Kim, 2020 ). The MIX used in the previous studies contained relatively small amounts of HE, whereas the MIX used in this experiment contained 25% HE.…”
Section: Discussionmentioning
confidence: 99%
“…These wastes from hatchery facilities are known as hatchery byproducts [ 2 ] and are regarded as alternative protein sources in nursery pig diets. A hatchery byproduct mixture could replace animal protein sources without compromising growth performance of nursery pigs [ 3 ]. For these reasons, the use of hatchery byproducts in swine diets would be both economically and environmentally beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, hatchery by-products are allowed in many countries including the United States and the European Union in animal feeds [ 4 , 10 ]. Nutrition studies revealed that properly processed HW can be a cheaper and very good substitute for animal protein sources such as fish meal and spray-dried plasma protein in animal feeds [ 1 , 2 , 5 , 9 , 11 ]. However, the high moisture content (MC) of the wastes and the specificity and presence of numerous microorganisms make it a highly unstable material.…”
Section: Introductionmentioning
confidence: 99%